Diversity of soil mite communities (Acari) within habitats seasonally flooded by the Vistula River (Ostromecko, Poland) - Kaczmarek, Sławomir; Marquardt, Tomasz; Faleńczyk-Koziróg, Katarzyna; Marcysiak, Katarzyna (Biological Letters, 2013)
The research was carried out in three types of habitats located in the seasonally flooded area of the Vistula River within Wielka Kępa Ostromecka Reserve: Salicetum albo-fragilis, Fraxino-Alnetum and Populetum albae. In the soil of Salicetum albo-fragilis Veigaia nemorensis and Trichouropoda ovalis were abundant, while Fraxino-Alnetum was dominated by Rhodacarellus silesiacus, and Populetum albae was overwhelmed by Rhodacarellus silesiacus and Dinychus inermis. Only between the Mesostigmata communities populating Fraxino-Alnetum and Populetum albae there were no statistically significant differences recorded in the distribution of abundance. The most similar, from the qualitative, quantitative and qualitative-quantitative point of view were Mesostigmata communities inhabiting Fraxino- Alnetum and Populetum albae. The numerous occurrence of Rhodacarellus silesiacus population in the soil of Fraxino-Alnetum and Populetum albae is most probably the result of succession changes within those habitats, and the species itself can be seen as an indicator of those habitats undergoing the process of a riparian forest transforming into an oak-hornbeam forest vegetation type.